2010
DOI: 10.1007/s10142-010-0184-1
|View full text |Cite
|
Sign up to set email alerts
|

Germin-like proteins (GLPs) in cereal genomes: gene clustering and dynamic roles in plant defence

Abstract: The recent release of the genome sequences of a number of crop and model plant species has made it possible to define the genome organisation and functional characteristics of specific genes and gene families of agronomic importance. For instance, Sorghum bicolor, maize (Zea mays) and Brachypodium distachyon genome sequences along with the model grass species rice (Oryza sativa) enable the comparative analysis of genes involved in plant defence. Germin-like proteins (GLPs) are a small, functionally and taxonom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 109 publications
3
52
0
3
Order By: Relevance
“…A large number of GLP genes have been discovered by genome sequencing or by expressed sequence tags (ESTs) in higher plants like Arabidopsis (Carter et al 1998;Membré et al 1997), barley (Druka et al 2002;Wu et al 2000), rice (Carrillo et al 2009;Membré and Bernier 1998), and peanut (Chen et al 2011). The closely related GLPs from different cereal genomes available in a public database were compared in a review by Breen and Bellgard (2010). The review also discussed the importance of GLP family members in plant defense due to the overlapping of some of the GLP cluster with the disease-resistance quantitative trait loci (QTL).…”
Section: Glp Gene Family Membersmentioning
confidence: 99%
“…A large number of GLP genes have been discovered by genome sequencing or by expressed sequence tags (ESTs) in higher plants like Arabidopsis (Carter et al 1998;Membré et al 1997), barley (Druka et al 2002;Wu et al 2000), rice (Carrillo et al 2009;Membré and Bernier 1998), and peanut (Chen et al 2011). The closely related GLPs from different cereal genomes available in a public database were compared in a review by Breen and Bellgard (2010). The review also discussed the importance of GLP family members in plant defense due to the overlapping of some of the GLP cluster with the disease-resistance quantitative trait loci (QTL).…”
Section: Glp Gene Family Membersmentioning
confidence: 99%
“…Manosalva et al (2009) reported that a GLP gene member located on chromosome 8 in rice provides resistance against rice blast and sheath blight disease. GLPs were studied by comparing the gene clustering in cereal genomes with rice, the model plant among grass species (Breen and Bellgard 2010). It was shown that the overlapping of gene clusters with specific QTLs associated with disease resistance contributes against pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to a true germin subfamily, both GLP1 and GLP2 subfamilies are limited to proteins of SOD action, while GLP3 is involved in phosphodiesterase activities. However, recently more subdivisions were suggested (Breen and Bellgard, 2010). A key feature of the germin and GLP subdivisions was the conservation of a motif derived from that of the cupin superfamily Thornburg, 1999, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Most of them share biochemical features such as sucrose-binding, globulins, and seed storage proteins, though they differ in their enzyme activities and tissue specificities (Kim et al, 2004). GLPs have been found in seeds, flowers, embryos, cotyledons, roots, stems, and leaves and were shown to be involved in several essential processes including apoptosis, defense, photoperiodic oscillation, development, and osmotic regulation (Mahmut, 2000;Breen and Bellgard, 2010). TATA box-binding protein (TBP) is a general eukaryotic transcription factor that is required by all three eukaryotic RNA polymerases for correct initiation of transcription of messenger, transfer, ribosomal, and small nuclear RNAs.…”
Section: Introductionmentioning
confidence: 99%